Assessment of tilt and decentration of a 4-point scleral fixated intraocular lens using an innovative digital measurement methodology - Denise Pardini; Monica MS Matsumoto; Marina Roizenblatt; Ana Marisa Branco; Paulo Schor; Norma Allemann; Michel Farah; André Maia; Maurício Maia (International Journal of Retina and Vitreous)
Abstract Background The study underscores the importance of conducting objective measurements of intraocular lens (IOL) tilt and decentration over time to provide evidence of IOL stability. The goals were to validate a new method for measuring tilt and decentration of secondary implants and evaluate the postoperative functional and anatomic outcomes of 4-support IOL scleral fixation. Methods This prospective study (7 patients, seven eyes) was conducted from October 2020 to April 2021 at the Department of Ophthalmology, Federal University of São Paulo, São Paulo, and Technological Institute of Aeronautics, São José dos Campos, Brazil. The patients underwent combined vitrectomy and implantation of a 4-point scleral fixation IOL. The subjective refraction with the logarithm of the minimum angle of resolution (logMAR) best-corrected visual acuity (BCVA), slit-lamp examination, Goldmann applanation tonometry, wide-field retinography, and Scheimpflug corneal tomography and topography were performed preoperatively and postoperatively. Macular optical coherence tomography (OCT) was performed to assess the presence of macular edema. Anterior-segment OCT and ultrasound biomicroscopy (UBM) were performed to measure IOL positioning. The method for measuring IOL positioning was validated. Surgery outcomes included BCVA, refraction, and IOL tilt and decentration. Results High intra-class correlations (0.781 to 0.999) were found for the intra- and inter-observer measurements of the UBM and OCT images. Measurements obtained using the scleral spur (SS) as an anatomic reference are comparable to those obtained using the iris pigmented epithelium (IPE) plane as a reference. Conversely, the measurements taken with OCT images cannot be compared to those obtained with UBM images. The logMAR BCVA improved from 0.59 ± 0.13 preoperatively to 0.24 ± 0.34 at 6 months postoperatively (P = 0.001). The mean tilt using anterior-segment OCT was 1.15 ± 1.26 degrees. The mean decentration on UBM images was 0.58 ± 0.63 mm; no significant changes in IOL position were observed between 1 and 6 months postoperatively. Conclusion The methodology exhibits strong reproducibility and enabled valid comparisons of tilt and decentration across the SS and IPE. Four-support IOL scleral fixation yields favorable surgical outcomes with physiologic IOL position and maintains stability throughout the follow-up period. Trial registration The Federal University of São Paulo institution’s Research Ethics Committee reviewed and approved this study protocol (Approval Number, 4.261.258).